2017
DOI: 10.2134/agronj2017.01.0020
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Mineral Nitrogen Fertilizer on Irrigated Maize and Soil Properties

Abstract: Core Ideas Grain yield, biomass, N uptake, SPAD units, soil N levels and N efficiciencies were affected by the N application rate. Maximum grain yields required 203 kg N ha−1 of available N in the 0‐ to 30‐cm layer soil. Sampling to a depth of 0 to 30 cm provided similar correlations than sampling to 0 to 60 and 0 to 90 cm. Mineral N fertilization increased soil organic C stock. Nitrogen is a key determinant of growth and grain yield (GY) in maize (Zea mays L.) and is therefore economically and environmentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Different studies have focused on N fertilization strategies in irrigated maize under Mediterranean conditions (e.g. Martínez et al, 2017;Berenguer et al, 2009). However, to our knowledge none of them have tested the performance of conservation tillage and its interaction with N fertilization on irrigated maize productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have focused on N fertilization strategies in irrigated maize under Mediterranean conditions (e.g. Martínez et al, 2017;Berenguer et al, 2009). However, to our knowledge none of them have tested the performance of conservation tillage and its interaction with N fertilization on irrigated maize productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Optimum SD vary from one environment to another [8]. In the Ebro valley, the month of April is the most recommended sowing period for maize, particularly, the first half of the month [20][21][22]. Even so, there can be year-to-year variations associated with temperatures and rainfall during spring.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, Al-Kaisi and Yin (2003) suggested that the traditional application rate used by farmers in north eastern Colorado in maize production (250 kg N ha -1 ) could be reduced to 140 kg N ha -1 without losses in grain yield, since high N rates led to a decrease in nitrogen use efficiency as soil water content decreased. Similarly, in a maize experiment in the NE Spain comparing different mineral N application rates, Martínez et al, (2017) reported that the lowest N fertilization rate sufficient to achieve optimal yields was 200 kg N ha -1 . In our experiment, in all the three years studied, the NUE and the NAR decreased when increasing the rate of N from 200 to 400 kg N ha -1 , obtaining an improvement of 47% in NAR when 200 kg N ha -1 were applied compared with 400 kg N ha -1 .…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the most effective means to ensure high yields while reducing N loss and thus environmental damage is to improve the nitrogen use efficiency (NUE) of crops (Davidson et al, 2015). In a long-term irrigated experiment with maize managed under CT and comparing different mineral N rates (0,100,150,200,250,300 and 400 kg N ha -1 ) also in the Ebro valley, Martínez et al (2017) observed the highest NUE and grain yield when applying 200 kg N ha -1 . Therefore, in the study area, it is feasible the reduction in maize N fertilization while maximizing maize yields.…”
mentioning
confidence: 99%